Sikap Indonesia dalam Penyelesaian Konflik Perpindahan Ibu Kota Israel dari Tel Aviv Ke Yerusalem di PBB (2014-2019) - Adettia Gama (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study is to identify and describe the role played by Indonesia in resolving the conflict over the transfer of Israel's capital city from Tel Aviv to Jerusalem at the United Nations from 2014 to 2019. The research method uses qualitative methods with a literature study approach by accumulating various information from the results of studies. beforehand as well as reviewing official documents and mass media regarding the status of Israel and Palestine in the international system. This study uses the concept of National Roles analysis from K. J. Holsti. The research results show that Indonesia acts as a Bastion of Revolution Liberator or a state that acts to eliminate colonialism or anti-colonial attitudes and the same ideological principles maintain peace without using a desire for ethnic unity or a military approach. The conclusion is that Indonesia is still consistent in supporting the existence of Palestine with a soft power or diplomacy approach. Keywords: Anti-Colonial Attitudes, Ideological Principles, Indonesia, Jerusalem, National Roles Conception